Ecological monitoring network for the Gulf of Finland. - Smirnova, Oksana; Popovich, Tatiana (My University, 2017)
Ecological situation in the Baltic region has notably worsened in the last 20 years. On the one hand, public organizations are bringing investments in order to build clear transport, green cities, to lower energy consumption in the region. On the other hand, construction of a new building of Leningrad Nuclear Power Plant not far from St. Petersburg is planned in the nearest future. In order to control the level of air pollution, to study the impact of pollution on the environment, to identify the most endangered regions, we would like to propose a new permanent ecological monitoring network for the Gulf of Finland. We hope this network will join together environmental specialists from different countries, which will allow to design a global ecological monitoring network. The major tasks for this network are the following: organization of ecological monitoring for the Baltic region and research of air pollution distribution along the Baltic sea; assessment of affects on the environment, health risks for atomic power plant staff and inhabitants of the nearest regions (North-West Russia, Estonia, Finland, Sweden); investigation of seasonal and daily changes of atmospheric temperature, pressure, humidity, wind and their effect on distribution of air pollution; creation of specialized social network for environmental scientists for data and research exchange. An example of ecological monitoring network operation in the Gulf of Finland along with description of means and results of monitoring are given in this paper.
Keywords: Küstenregion; Kooperative Regionalplanung; Grenzüberschreitende Kooperation; Umweltschutz; Naturschutz; Umweltmonitoring